Experimental Investigation and Mathematical Modelling of Pressure Response for Steam Generator - A. AbdulKareem, Mishaal (International Journal of Engineering and Technology, 2018)
Cold startup of boiler is the process of boiler operation with water at ambient temperature and pressure with all intake and discharge valves are fully closed to permit fast development of pressure.Â  A mathematical model is developed to estimate the pressure response during cold startup of a perfectly insulated steam generator unit. A commercial type pressure switch is used in this unit to control and maintain the desired set point of the steam operating pressure. This mathematical model assume that the thermal properties of the supplied liquid water are temperature dependent. It is based on a novel Pressure Marching Technique that is coded using a FORTRAN language computer program. The maximum percentage error of (8.24 %) was obtained when comparing the predicted results of the mathematical model with the measured values obtained from the experimental test that was done using a (2 kW) electric steam generator unit with a volume of (30 litter) and maximum operating pressure of (8 bar). In addition, the same behavior of the predicted results was obtained when compared with results of a previously published article. It was found that the time constant of the pressure control system is directly proportional with its operating pressure set point and with the volume of the steam generator and its void fraction. A (50%) increase in the pressure set point will increase the time constant by (66.16%). Increasing the boiler volume by (166.667%) will increase the time constant by (166.677%) and increasing the boiler void fraction by (150%) will increase the time constant by (23.634%). The time constant is inversely proportional with the heating power of the steam generator. A (100%) increase in the heating power will decrease the time constant by (50%). The time constant is independent of the initial water temperature. Also, it was found that the time delay to start water evaporation is directly proportional with the volume of the steam generator. A (166.667%) increase in boiler volume will increase the time delay by (166.65%). The time delay is inversely proportional with the initial water temperature and with the heating power and void fraction of the steam generator. A (38.889%) increase in the initial water temperature will decrease the time delay by (8.882%). Increasing the heating power by (100%) will decrease the time delay by (50%) and increasing the boiler void fraction by (150%) will decrease the time delay by (16.665%). The time delay is independent on the operating pressure set point.Â Â